Undergraduate business students perceptions of teaching presence in online business courses - Finley, Lacey (Kansas State University, 2016)
The purpose of this case study was to explore Teaching Presence in the undergraduate online Business course environment. This study explored the following three Research Questions: 1. How do undergraduate Business students perceive Teaching Presence in online courses? 2. What Teaching Presence components do undergraduate Business students find valuable in online courses? 3. How do exemplary undergraduate online Business course faculty demonstrate Teaching Presence in online instruction? The population of this study consisted of 20 undergraduate Business students and 3 student-nominated Business faculty. Participants included Business students enrolled in online Business courses. Based on the student interviews, the faculty most often nominated by the students as demonstrating effective methods of Teaching Presence in online Business courses served as faculty participants. Interviews of students and faculty were conducted during the Fall 2015 semester. There were 101 units identified for Research Question 1, with 46 units for the theme of "Direct Instruction", 36 for the theme of "Discourse Facilitation", and 19 units for the theme of "Design and Organization". The major findings from these research questions were that undergraduate Business students perceived online course Teaching Presence most through Direct Instruction. Students perceived prompting student engagement in discussions and encouraging student participation as important elements of the "Discourse Facilitation" theme. Students perceived good course design methods as being important to Teaching Presence. There were 245 units identified for Research Question 2, with 93 units for the theme of "Design and Organization", 88 units for "Discourse Facilitation" and 64 units for Direct Instruction". The major findings were that the "Design and Organization" theme was found to be most valuable to undergraduate Business students in the form of designing methods and establishing time parameters. Setting a climate for learning within the "Discourse Facilitation" theme and confirming understanding within the "Direct Instruction" themes were important to students when discussing what Teaching Presence components they found valuable in online Business courses. There were 81 units identified for Research Question 3, which consisted of faculty interviews focused on how exemplary online Business course faculty demonstrated Teaching Presence. The themes that were found in the faculty interviews were 30 units for the "Design and Organization" theme, 26 units for the "Discourse Facilitation" theme and 25 units for the "Direct Instruction" theme. The major findings were that the "Design and Organization" theme was found to be of the utmost importance to exemplary faculty when discussing the demonstration of Teaching Presence in online Business courses. Within the "Discourse Facilitation" theme, faculty emphasized the importance of drawing in participants and prompting discussion. Confirming understanding was found to be the most important aspect of the "Direct Instruction" theme. Recommendations for the research setting were in the areas of learning activity clarity, the use of integrated video lectures, enriched student-instructor interaction strategies, and technological tools to identify student comprehension struggles. Recommendations for future research including a study of Teaching Presence in different academic disciplines and in different academic environments, the efficacy of various technologies in enhancing Teaching Presence, and instructor attributes influencing Teaching Presence.
Keywords: Teaching presence; Business education; Online education; Higher education; Student perceptions